2009
DOI: 10.1063/1.3262612
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution cavity ringdown spectroscopy of the jet-cooled ethyl peroxy radical C2H5O2

Abstract: We have recorded high resolution, partially rotationally resolved, jet-cooled cavity ringdown spectra of the origin band of the A-X electronic transition of both the G and T conformers of the perproteo and perdeutero isotopologues of the ethyl peroxy radical, C(2)H(5)O(2). This transition, located in the near infrared, was studied using a narrow band laser source (< or approximately 250 MHz) and a supersonic slit-jet expansion coupled with an electric discharge allowing us to obtain rotational temperatures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 42 publications
(46 reference statements)
1
39
0
Order By: Relevance
“…In addition, these equations can be employed to derive the relation of SR constants upon isotopic or chemical substitution, 67,68,70 and to predict SR constants of a substitution using a reference molecule with known SR constants. 27,71,72 In such calculations, the mass-independent SR constant ' ε is assumed to be invariant upon substitution.…”
Section: Sr Constantsmentioning
confidence: 99%
“…In addition, these equations can be employed to derive the relation of SR constants upon isotopic or chemical substitution, 67,68,70 and to predict SR constants of a substitution using a reference molecule with known SR constants. 27,71,72 In such calculations, the mass-independent SR constant ' ε is assumed to be invariant upon substitution.…”
Section: Sr Constantsmentioning
confidence: 99%
“…[12][13][14] Blanksby et al 15 have reported the photoelectron (PE) spectra of the CH 3 OO and C 2 H 5 OO anions, finding the electron affinities of the corresponding radicals to be 1.161 ± 0.005 eV and 1.186 ± 0.004 eV, respectively. Theà ←X electronic transitions of CH 3 OO and C 2 H 5 OO in the near-IR absorption region have been characterized by Miller and co-workers [16][17][18] using cavity ringdown spectroscopy. For both radicals, ground state andà state rovibronic structures were observed and identified.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Details about the present experimental work not described in the previous papers will be described in this section.…”
Section: Methodsmentioning
confidence: 99%
“…However, the excitedà electronic state is bound and produces spectra that distinguish among different chemical species and their isomers and conformers because of the sharp vibrational and rotational structure. 4 Jet cooled high-resolution cavity ringdown spectroscopy (CRDS) studies on peroxy radicals [5][6][7] are useful for diagnostic purposes, experimentally characterizing the molecule, and benchmarking quantum chemical calculations. 8 The β-hydroxyethylperoxy (2-hydroxyethylperoxy) radical in the atmosphere arises from the reaction of ethene (CH 2 CH 2 ) and hydroxy radical (OH), followed by reaction with oxygen (O 2 ).…”
Section: Introductionmentioning
confidence: 99%